2018
DOI: 10.1111/bjp.12350
|View full text |Cite
|
Sign up to set email alerts
|

One Language and Two Mother Tongues in the Consulting Room: Dilemmas of a Bilingual Psychotherapist

Abstract: The purpose of the present study is twofold: first, to explore the bilingual therapist's experience of working in a second language; and second, to explore the major functions of language within the therapeutic setting. Interpretative phenomenological analysis is used to explore in depth the experience of 16 bilingual therapists of different professional orientations: psychoanalysts, psychotherapists, counselling psychologists, clinical psychologists and counsellors. Semi-structured life-world interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Jimanez (2004) also suggests, that his recent acquisition of the German language made him more alert to literal meanings overlooked by native speakers. Gulina and Dobrolioubova (2018) bring similar findings, suggesting that polyglot therapists sometimes find themselves more alert to unique verbalisation, slips of tongue and double meaning in a foreign language.…”
Section: Further Thoughtsmentioning
confidence: 52%
See 2 more Smart Citations
“…Jimanez (2004) also suggests, that his recent acquisition of the German language made him more alert to literal meanings overlooked by native speakers. Gulina and Dobrolioubova (2018) bring similar findings, suggesting that polyglot therapists sometimes find themselves more alert to unique verbalisation, slips of tongue and double meaning in a foreign language.…”
Section: Further Thoughtsmentioning
confidence: 52%
“…Taking a research approach to the issue of polyglot therapists, Gulina and Dobrolioubova (2018) bring findings from a study exploring experience of foreign therapists that moved to a new country at an earlier stage in their careers, and went through their professional training in English. The researchers found that for polyglot therapists, language had many aspects; vocabulary, cultural background, behavioural differences, meaning, feeling, tonality, symbolism and communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of language and its impact in working therapeutically with clients from CaLD backgrounds has been recognised for decades, both in the United Kingdom (Bager-Charleson, Dewaele, Costa, & Kasap, 2017;Bowker & Richards, 2004;Costa, 2010;Gulina & Dobrolioubova, 2018;Itzhak, Vingron, Baum, & Titone, 2017;de Zulueta, 1990) and the United States (Burck, 2004;Hodes, 1989;Marcos, 1976;Santiago-Rivera, 1995;Santiago-Rivera & Altarriba, 2002;Santiago-Rivera et al, 2009). Despite the frequency of bilingual and multilingual families presenting for therapy, limited research has addressed issues related to differences in language between therapist and the family, and there is less about the implications of family members speaking two or more languages, the major themes identified being: 'listening and understanding the client'; 'interventions and interpretations'; 'potential impact of language on the therapeutic encounter: therapist's point of view'; and 'therapist's experience of self' (Gulina & Dobrolioubova, 2018).…”
Section: Impact Of Bilingualism and Multilingualism In Therapymentioning
confidence: 99%
“…Additionally, as Aranda (2016) suggests, the commitment of achieving cultural competence when working with immigrants extends to interpreters, as language barriers are frequently present when working with immigrant populations, and thus, translation services are routinely utilized. Lastly, issues related to language (e.g., monolingualism, bilingualism, multilingualism) may have more significant impact than previously understood in counseling research in various areas including emotional expression, power dynamics, psychological flexibility, identity formation and memory encoding (see Costa & Dewaele, 2018 for a review), for both the client as well as the therapist (Gulina & Dobrolioubova, 2018), especially when trauma treatment is performed (Costa & Dewaele, 2018).…”
Section: Group Cpt As a Treatment For Immigration Traumamentioning
confidence: 99%